REKONTEMPLASI PERAN DEWAN PERS DAN INDEPENDENSI PERS - Fardiyan, Ahmad Rudy (JURNAL SOSIOLOGI, 2014)
This study discusses the role of the Press Council as an protector of agency press institutions in Indonesia. As a public institution, the press does not escape from the push-pull various issues of public interest. Press Council as an independent body, is appropriate to give a big share in maintaining the integrity of the press in relation to public kepentinga. The method used in this study is a review of the literature. The conclusion is that in many cases that have occurred in Indonesia, we need to scrutinize the role of the Press Council in establishing the atmosphere of objective information and in favor of the public interest.